Anthropology in a Globalized World. History, Culture and Philosophy - Wulf, Christoph (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
Today’s anthropology attempts to relate the historicity and culturality of its concepts, viewpoints, and methods to the historicity and culturality of what is under investigation. Anthropology examines the findings of the human sciences and develops a critique of itself based on historical and cultural philosophy, thereby paving the way for the investigation of new questions and issues. At the heart of these efforts lies a restlessness of mind that cannot be stilled. Research in anthropology is not limited to certain cultural contexts or single epochs. Reflections on the integral historicity and culturality of the research enable the discipline to leave behind the Euro-centricity of the human sciences and to focus on the unresolved problems of the present and the future.
Keywords: cultural anthropology; educational anthropology; historical anthropology; hominization; philosophical anthropology